The Lithuanian Language and Political Self-Awareness of the Grand Duchy of Lithuania: Evidence from Eighteenth-Century Texts - Kuolys, Darius (Senoji Lietuvos literatūra, 2025)
The article examines texts in Lithuanian published in the eighteenth-century Grand Duchy of Lithuania from the perspective of political consciousness, taking into account their political and cultural contexts. At the same time, the study considers Jurgis Lebedys’s hypothesis that throughout the eighteenth century, the tradition of caring for the Lithuanian language remained alive in the Grand Duchy of Lithuania, and that there is a connection between the programme for the Lithuanisation of the state of Lithuania proposed by Mikalojus Daukša in the sixteenth century and the Samogitian and Lithuanian national movements that emerged in the early nineteenth century.In the eighteenth century, the culture of the Grand Duchy of Lithuania was influenced by the historical narrative of Maciej Stryjkowski and Albertas Kojalavičius, which depicted Lithuania as a Lithuanian-speaking Republic of Lithuania founded by the Lithuanian people, ruled by sovereigns of Lithuanian descent, and belonging to the Lithuanian nobility. Throughout the eighteenth century, popular seventeenth-century Lithuanian religious books, such as hymnals, prayer books, and collections of Gospel passages, were continuously reprinted in the Grand Duchy of Lithuania. The original Lithuanian hymns and prayers in those books affirmed the connection between the Lithuanian-speaking community and the state of Lithuania; they united Lithuanians of different estates, who were protected by St Casimir, into a single nation and linked them to their homeland: ‘the land of Lithuania’, ‘the land of Lithuania and Samogitia’, ‘the Duchy of Samogitia’, ‘the Duchy of Lithuania and Samogitia’, and ‘the country of the Poles, Lithuanians, and Samogitians’.The connection between the Lithuanian language and the state is emphasised even more strongly in the new Lithuanian books and publications on Lithuanian studies that appeared in the eighteenth century. The 1737 Lithuanian grammar Universitas Lingvarum Litvaniae declares the Lithuanian language as the language of Lithuania and asserts that the Grand Duchy of Lithuania has a ‘main dialect’, and that this dialect has well-defined ‘grammatical rules’ that enable the description of ‘the entirety of the languages of Lithuania’. The anonymous author and the publisher, the printing house of Vilnius Academy, dedicated this entirety of languages to the descendants of Palemon, the legendary Lithuanian ancestor. The grammar book declares that not only Lithuanian nobles and gentry, but all young studying Lithuanians, as well as all readers of that book and all inhabitants of the Grand Duchy of Lithuania who speak the Lithuanian language are the ‘diligent neo-Palemons’. We can therefore rightly regard the author of the grammar as a conscious successor to Daukša’s political programme.The publication of new books in Lithuanian and on Lithuanian studies in the early eighteenth century coincided with a surge of Lithuanian patriotism in the public life of the Grand Duchy of Lithuania. It was precisely at that time that the term ‘Republic of the Grand Duchy of Lithuania’ (Rzeczpospolita W. X. Lit.), a term describing the political nation of the Grand Duchy and the nobility, began to be used emphatically in official state documents and in sejmiks, and the idea of the Republic of Lithuania, along with the affirmation of Lithuania’s political independence, was once again brought to the attention of the public. In books, lectures, and exercise books published by Vilnius Academy, Lithuania is increasingly referred to as ‘Palemonia’, ‘the Land of Palemon’, ‘the world of Palemon’ (Palaemonia, Palaemonius orbis, Palemoński świat), Lithuanians as ‘the people of Palemon’ (Palaemonia gens), and Vilnius University as ‘Palemon’s Academy’.In the mid-eighteenth century, the printing house of Vilnius University began publishing a textbook of the Lithuanian language, which was continuously reprinted in ever-growing print runs. Over the decades, the textbook and the rising number of old and new religious books in Lithuanian cultivated the Lithuanian-reading part of the public of the Grand Duchy of Lithuania. During the Age of Enlightenment, this segment of people, together with the even larger part of Lithuanian speakers, was neither ignored nor silenced.Lithuanian intellectuals of the late eighteenth century turned their attention to ploughmen and peasants and elevated their role in the life of the nation. Their efforts to integrate the peasants into the political nation were accompanied by the efforts to ‘Lithuanise’ the Grand Duchy and revive the ‘peasant language’. As evidenced by the increasingly frequent use of ‘the Lithuanian Nation’ (Naród Litewski) in state documents and other texts, as well as the emphasis on the sovereignty of the state of Lithuania and its nation, these aspirations are also linked to the resurgence of Lithuanian patriotism during the twilight of the Grand Duchy of Lithuania. While the Four-Year Sejm of the Polish-Lithuanian Commonwealth was still in session, the Constitution of 3 May 1791 and several laws passed by the Sejm were translated into Lithuanian.A turning point in the public life of the Grand Duchy of Lithuania occurred during the uprising of 1794: the urban and peasant estate entered the political arena, and the government began to use the Lithuanian language alongside Polish as the language of communication with its citizens. Based in Vilnius, the leadership of the country’s rebels – the Supreme Council of the Lithuanian Nation – addressed all residents of the Grand Duchy of Lithuania with an appeal that was not only in Polish but also in Lithuanian – Aciszaukimas. The term ‘the Republic of Lithuania’, which was used in the first half of the eighteenth century, was replaced by ‘the Lithuanian Nation’, but the idea of the sovereign society of the Grand Duchy of Lithuania remained fundamental: it permeated all the texts of the uprising that were printed in Vilnius. At the time, the government published Tadeusz Kościuszko’s ‘Proclamation’, various orders, a sermon by Mykolas Pranciškus Karpavičius (Michał Franciszek Karpowicz), a professor at Vilnius University, explaining the purpose of the uprising, and the text of the oath addressed to all residents of the Grand Duchy of Lithuania in Lithuanian. Lithuanian rebel war songs were being composed. The idea of a political nation of free and equal people was being promoted in Lithuanian. After the collapse of the Grand Duchy of Lithuanian, the connection between the Lithuanian language and the Lithuanian nation, as asserted in eighteenth-century Lithuanian texts, was noted and highlighted by the country’s intellectuals at the beginning of the nineteenth century: Pranciškus Ksaveras Bogušas (Franciszek Ksawery Bohusz), Simonas Stanevičius, and Simonas Daukantas.
Keywords: Lithuanian language; Lithuanian nation; political consciousness; political vocabulary; religious texts; Age of Enlightenment; uprising of 1794